Notes on phytosociology of Juniperus excelsa in Macedonia (southern Balkan Peninsula) - Matevski, V.; Carni, A.; Kostadinovski, M.; Marinsek, A.; Mucina, Ladislav; Pausic, A.; Silc, U. (Versita, 2010)
Juniperus excelsa is an East Mediterranean species found also in marginal, sub-mediterranean regions of the southern part of the Balkan Peninsula. It prefers shallow soils in the warmest habitats of the zone of thermophilous deciduous forests. In the past the rank of alliance and the name of Juniperion excelsae-foetidissimae have been suggested for the vegetation dominated by Juniperus excelsa in the Balkan Peninsula. In this paper we present the valid description of the alliance in accordance with the International Code of Phytosociological Nomenclature. The validation of the Juniperion excelsae-foetidissimae required description of a new association - the Querco trojanae-Juniperetum excelsae. The Juniperion excelsae-foetidissimae is classified within the order of Quercetalia pubescentis Klika 1933 (the Quercetea pubescentis Doing-Kraft ex Scamoni et Passarge 1959).